Influence of construction interface management practice on project performance in Nigeria - Ekung, S.; Lashinde, A. (Penerbit Universiti Kebangsaan Malaysia, 2018)
To curb community influences on construction project performance at the delivery stage, a number of interface management practices (IMP) are increasingly adopted. This study determined the impact of these practices on project time performance. The objectives were to determine the effectiveness of identified IMP, their level of use, and impacts on timely project delivery. The study adopted a mixed research approach involving semi-structured interview and questionnaire survey conducted in South-South and South-East, Nigeria. Data obtained from 127 stakeholders in 66 project cases were analysed using percentages and canonical correlation analysis. The results indicated that five out of 13 interface management practices validated were prevalently used in the study area, four of which are effective to achieve timely project delivery. The result also established a significant positive correlation between these practices and project time performance. The study concludes that early community involvement, use of community liaison person, communication management, and stakeholder management are important community-project organisation interface management practices with significant impacts on project time performance. The study recommends practices of hybrid application of one or more methods for optimal result based on varying levels of performance.